Insula Volume in Patients Diagnosed with Obsessive Compulsive Disorder and its Relation with Clinical Variables - Yildiz, Sevler; Ugur, Kerim; Taskent, Ismail; Atmaca, Murad (Turkish Neuropsychiatry Assoc-Turk Noropsikiyatri Dernegi, 2020)
Introduction: Neuroimaging studies performed in recent years on patients with obsessive compulsive disorder have determined anomalies that are possibly associated with the determinant signs and symptoms of the disease. The purpose of this study is to investigate the morphometric changes in insula volume and related parameters in order to understand the etiopathogenesis of obsessive compulsive disorder better. Method: Throughout the study, 20 patients eligible for the study criteria, who were diagnosed with OCD according to DSM-5 diagnostic criteria and receiving inpatient or outpatient treatment after applying to Firat University Hospital Psychiatry Department, and 13 healthy subjects in the control group have been included in the study. Sociodemographic and Clinical Data Form, Hamilton Depression Rating Scale (HAM-D), Hamilton Anxiety Rating Scale (HAM-A), Yale-Brown Obsession Compulsive Scale (Y-BOCS) and SCID-I have been applied to the patients. Volumetric measurements were performed on the insula by using magnetic resonance imaging (MRI) in patient and control groups. Results: No significant difference was observed between patients with Obsessive Compulsive Disorder and healthy controls with regard to insula volume. Discussion: It may be stated that insula may be associated with both the pathophysiology and clinical course of the disease. It is suggested that studies considering the imaging methods examining the functional characteristics of this area and tests on cognitive functions together may lead to significant and efficient results.
Keywords: Obsessive compulsive disorder; volume; insula; MRI